Chemically resistant silicon-based PC-PBT-ABS ternary alloy material and preparation method thereof
Patent Information
- Application Number
- CN202611261030.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-19
- Publication Date
- 2026-10-16
AI Technical Summary
硅橡胶粒子及小分子硅油等硅系助剂本质上属于非极性材料,而PC、PBT、ABS基体则具有较强的极性特征,二者之间热力学相容性较差,硅系助剂在合金熔体中难以实现均匀、稳定的纳米级分散,易发生团聚、析出或界面脱粘,导致增韧效果不稳定,且易在相界面处形成缺陷,反而成为应力开裂的诱发源;
1、通过EMA-g-GMA与硅烷偶联剂改性云母粉协同增韧,以及聚硅氧烷链段化学键合引入PC主链,实现了硅系助剂在极性基体中的分子级均匀分散与稳定界面结合,解决了传统物理共混导致的团聚、析出、界面脱粘及相界面缺陷诱发应力开裂的问题,增韧效果稳定可靠。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This application relates to the field of PC-PBT-ABS ternary alloy materials technology, and more specifically, to a chemically resistant silicon-based PC-PBT-ABS ternary alloy material and its preparation method. Background Technology
[0002] Polycarbonate possesses excellent impact toughness, heat resistance, and dimensional stability, but suffers from poor processing fluidity, insufficient chemical solvent resistance, and notch sensitivity. Polybutylene terephthalate (PET) is a crystalline polyester with outstanding chemical resistance, fuel resistance, and good molding and processing properties, but exhibits low notched impact strength and low-temperature brittleness. Acrylonitrile-butadiene-styrene copolymer (APT-ABS) combines a balanced mechanical property of toughness, hardness, and rigidity with excellent processing fluidity, surface gloss, and coating adaptability. Ternary alloying of these three resins can achieve a degree of performance complementarity, resulting in a PC-PBT-ABS alloy that combines the high toughness and heat resistance of PC, the chemical and fuel resistance of PBT, and the excellent processing fluidity of ABS. Therefore, it is widely used in automotive engine peripheral parts, new energy battery housings, power tool housings, and other applications requiring long-term resistance to chemical media such as engine oil, cleaning agents, and alcohol solvents.
[0003] However, ternary alloys of PC, PBT, and ABS still face problems such as significant low-temperature brittleness, high notch sensitivity, and chemically induced environmental stress cracking in practical applications. To improve these defects, existing technologies generally employ physical blending of silicone rubber particles, small-molecule silicone oil, and other silicon-based additives into the alloy matrix for modification. This primarily utilizes the extremely low glass transition temperature of siloxane segments to enhance the low-temperature impact toughness of the material, and leverages the microphase dispersion effect of the silicon phase in the matrix to alleviate localized stress concentration, thereby improving the alloy's stress cracking resistance to some extent. However, the above-mentioned silicon-based physical blending modification scheme still has the following problems in practical applications and mass production: Silicone rubber particles and small molecule silicone oils and other silicone additives are essentially non-polar materials, while PC, PBT and ABS matrices have strong polar characteristics. The thermodynamic compatibility between the two is poor. Silicone additives are difficult to achieve uniform and stable nanoscale dispersion in alloy melts, and are prone to agglomeration, precipitation or interfacial debonding, resulting in unstable toughening effect. They are also prone to forming defects at the phase interface, which can become the inducing source of stress cracking. Adding silicon-based toughening agents to compensate for insufficient low-temperature toughness will significantly weaken the rigidity and heat deformation temperature of the alloy, causing the product to deform and fail under high-temperature load conditions. The addition of silicone additives often causes abnormal demolding behavior of the alloy melt and the mold surface, resulting in a decrease in the gloss of the product and an increase in surface roughness. Summary of the Invention
[0004] To address the aforementioned technical problems, this application provides a chemically resistant silicon-based PC-PBT-ABS ternary alloy material and its preparation method.
[0005] In a first aspect, this application provides a chemically resistant silicon-based PC-PBT-ABS ternary alloy material, employing the following technical solution: A chemically resistant silicon-based PC-PBT-ABS ternary alloy material is prepared from the following raw materials in parts by weight: Silicon-containing PC 47.5-61% ABS 8-10% PBT8-10% Modified toughening agent 1-2% 1-2% high-gluten powder Silicone powder 1-2% Flame retardant 7-10% 10-15% enhancer Antioxidant 0.5-1% Anti-dripping agent 1-2% The modified toughening agent is composed of EMA-g-GMA and silane coupling agent modified mica powder.
[0006] Preferably, the weight ratio of the EMA-g-GMA to the silane coupling agent modified mica powder is 5:1-2.
[0007] By employing the above technical solution, EMA-g-GMA and silane coupling agent are synergistically used to modify mica powder to form a toughening agent. The epoxy groups of EMA-g-GMA react chemically with the active groups such as hydroxyl and carboxyl groups in the PC, PBT, and ABS matrices, forming a chemically bonded interface between the silicon-based component and the polar matrix. This solves the problems of agglomeration, precipitation, and interfacial debonding caused by poor thermodynamic compatibility in traditional physical blending of silicone rubber particles or silicone oil. Simultaneously, the functional groups of the silane coupling agent molecules in the silane coupling agent-modified mica powder react chemically with the PC, PBT, and ABS matrix resins, thereby constructing a chemically bonded interface between the mica inorganic filler and the organic polymer matrix. This strong interfacial bonding ensures that under impact loads, the stress in the matrix can be efficiently transferred to the mica sheets, avoiding toughening failure due to premature interfacial debonding. Furthermore, the uniformly dispersed modified mica powder eliminates the agglomerates and localized stress concentration defects easily generated by unmodified fillers, ensuring stable toughening performance.
[0008] Furthermore, the introduction of silicone powder optimizes melt demolding behavior, and combined with the interfacial compatibilization effect of EMA-g-GMA, effectively improves the surface gloss and appearance quality of the product. Ultimately, the resulting ternary alloy maintains excellent chemical solvent resistance, fuel resistance, and flame retardant properties, making it suitable for applications such as automotive engine peripheral parts and new energy battery casings, where long-term resistance to chemical media such as engine oil, cleaning agents, and alcohol solvents is required, and where stringent requirements for mechanical properties, dimensional stability, and surface precision are necessary.
[0009] Preferably, the reinforcing agent is composed of cellulose nanocrystals, nanoclay, and nanorare earth oxides in a weight ratio of 10:4-7:1.
[0010] By adopting the above technical solutions, the reinforcing agent improves the tensile strength, flexural modulus, and rigidity of the alloy, resulting in excellent dimensional stability of the product under high-temperature load and a significantly increased heat distortion temperature. The synergistic effect of the lamellar barrier of nano-clay and the reinforcing network of cellulose nanocrystals effectively blocks the penetration of chemical media, enhancing resistance to chemical solvents, fuel oil, and environmental stress cracking. Nano-rare earth oxides improve the thermal stability and flame-retardant synergistic effect of the alloy, reducing the combustion heat release rate and increasing char formation; the nano-reinforcing network formed by these three components simultaneously improves notched impact strength and low-temperature toughness, achieving a multi-dimensional balance of rigidity, heat resistance, chemical resistance, and toughness.
[0011] Preferably, the cellulose nanocrystals, the nanoclay, and the nanorare earth oxides have different particle sizes.
[0012] By adopting the above technical solution, nanofillers of different particle sizes form a gradient-graded filling structure in the matrix. Large-sized particles provide skeletal support, medium-sized particles fill the gaps, and small-sized particles compact the interface, thereby improving the filler volume fraction and dispersion uniformity. The tensile strength, flexural modulus, heat distortion temperature, chemical resistance, and low-temperature toughness of the resulting alloy are synergistically enhanced, achieving an excellent balance between rigidity, heat resistance, and toughness, and improving the dimensional accuracy and appearance quality of the product.
[0013] Preferably, the silicon-containing PC is prepared by the following method: A1. Under vacuum conditions, bisphenol A is placed in a reaction vessel, heated to 160-180℃, and then slowly added with diester and catalyst. The reaction is maintained at this temperature for 3-5 hours to obtain mixture 1. A2. Under vacuum conditions, mixture 1, polysiloxane diol and zinc acetate are added to a reaction vessel. The temperature of the reaction vessel is raised to 220-240℃ and kept at this temperature for 4-6 hours. The resulting product is silicon-containing PC after post-processing.
[0014] Preferably, the raw materials used to prepare the silicon-containing PC are as follows by weight: 100 parts of Bisphenol A 100-105 parts of dicarbonate Catalyst 0.3-0.5 parts 15-20 parts of polysiloxane diol Zinc acetate 0.2-0.4 parts.
[0015] By adopting the above technical solution, bisphenol A and diester are first prepolymerized under the action of a catalyst to form polycarbonate oligomers. Then, polysiloxane diol is introduced and block copolymerized at 220-240℃ under the catalysis of zinc acetate. This allows flexible polysiloxane segments to be uniformly embedded into the PC backbone through chemical bonding, achieving molecular-level dispersion of siloxanes in the PC matrix. This avoids the problems of agglomeration, precipitation, interfacial debinding, and phase separation caused by traditional physical blending of silicon-based additives. As a result, while maintaining the original high impact toughness, high heat resistance, and good dimensional stability of polycarbonate, the material exhibits improved low-temperature impact toughness, a significantly reduced brittle transition temperature, and a markedly reduced notch sensitivity. Simultaneously, its resistance to chemical solvents, fuel oil, and environmental stress cracking is greatly enhanced. It also maintains high mechanical property retention after long-term contact with chemical media such as engine oil and cleaning agents, and the surface gloss of the finished product is excellent.
[0016] Preferably, the polysiloxane diol is composed of polysiloxane diol with a molecular weight of 3000-6000 and polysiloxane diol with a molecular weight of 6000-10000 in a weight ratio of 1:4-7.
[0017] By employing the above technical solution, in the polysiloxane diol compound system with different molecular weights, the low molecular weight component readily undergoes a uniform block reaction with the polycarbonate backbone, promoting the molecular-level dispersion of siloxane segments in the matrix and effectively improving compatibility and processing fluidity. The high molecular weight component provides longer and more flexible siloxane segments, lowering the glass transition temperature of the material and significantly improving low-temperature impact toughness and stress cracking resistance. The synergistic effect of the two components in a specific ratio allows silicon-containing PC to maintain high rigidity, high heat resistance, and dimensional stability while also possessing excellent low-temperature toughness, chemical solvent resistance, and good melt flowability, avoiding the agglomeration, precipitation, and interfacial debinding problems that are prone to occur in physically blended silicon-based additives.
[0018] Preferably, the silicon-containing PC content is 49.5%, the ABS content is 8%, and the PBT content is 10%.
[0019] By adopting the above technical solutions and optimizing the dosage of the three components, the alloy can be made to have high rigidity, high heat resistance, low temperature toughness and excellent forming and processing performance, thus achieving a multi-dimensional balance of mechanical properties, chemical resistance and processing performance.
[0020] Preferably, the flame retardant includes at least one of sulfonates, phosphates, and phosphonates.
[0021] By adopting the above technical solutions, the material is endowed with excellent flame retardant properties, low smoke density, high char formation, and effective suppression of dripping, achieving a flame retardant rating of V-0. Simultaneously, it exhibits good compatibility with silicon-containing PC, PBT, and ABS matrices, improving flame retardancy without compromising the material's mechanical properties, chemical resistance, or surface quality.
[0022] Preferably, the anti-dripping agent comprises at least one of polytetrafluoroethylene micropowder, PTFE-coated silicone rubber core-shell particles, siloxane-acrylate core-shell particles, and polyimide micropowder.
[0023] By adopting the above technical solutions, combustion droplets are effectively suppressed, dense carbon layer formation is promoted, flame retardancy rating is improved, secondary ignition risk is reduced, and good compatibility with the matrix is achieved without damaging the mechanical and surface properties of the material.
[0024] Secondly, this application provides a method for preparing a chemically resistant silicon-based PC-PBT-ABS ternary alloy material, using the following technical solution: A method for preparing a chemically resistant silicon-based PC-PBT-ABS ternary alloy material involves mixing silicon-containing PC, ABS, PBT, a modified toughening agent, high-rubber powder, silicone powder, a flame retardant, a reinforcing agent, an antioxidant, and an anti-dripping agent, then adding the mixture to a twin-screw extruder for extrusion granulation to obtain the chemically resistant silicon-based PC-PBT-ABS ternary alloy material.
[0025] Preferably, the processing temperature of the twin-screw extruder is 220-280℃, and the screw speed is 250-300rpm.
[0026] By adopting the above technical solution, a one-step melt extrusion granulation process using a twin-screw extruder is employed. Under strong shear, the components achieve uniform dispersion, effectively avoiding the agglomeration, precipitation, and interfacial debinding problems that easily occur in traditional physical blending. Simultaneously, the synergistic effect between the raw materials is fully utilized, resulting in a ternary alloy with excellent low-temperature toughness, rigidity, heat resistance, chemical solvent resistance, flame retardancy, and surface quality. This fully meets the dual requirements of material performance and production efficiency in high-end applications such as automotive engine peripheral parts and new energy battery casings. Furthermore, the process route is simple and efficient, requiring no pre-reaction or post-processing steps, resulting in a short production cycle, low energy consumption, and easy implementation for continuous, large-scale industrial production.
[0027] In summary, this application has the following beneficial effects: 1. By synergistic toughening of mica powder modified with EMA-g-GMA and silane coupling agent, and the introduction of polysiloxane segments into the PC backbone through chemical bonding, the molecular-level uniform dispersion and stable interfacial bonding of silicon-based additives in the polar matrix are achieved. This solves the problems of agglomeration, precipitation, interfacial debonding and stress cracking induced by phase interface defects caused by traditional physical blending, and the toughening effect is stable and reliable.
[0028] 2. The synergistic effect of the siloxane segments of silicon-containing PC and the crystalline chemical resistance of PBT, combined with the layered barrier effect of nano-clay and the strong interfacial bonding to block the penetration channels of chemical media, enables the alloy to maintain high mechanical properties after long-term contact with engine oil, cleaning agents, alcohol solvents and fuels, with no surface cracks or swelling, and excellent resistance to environmental stress cracking.
[0029] 3. By leveraging the lamellar rigidity support effect of mica powder modified by silane coupling agent, and the synergistic effect of the gradient nano-reinforcing network formed by cellulose nanocrystals, nano-clays and nano-rare earth oxides of different particle sizes, the tensile strength, flexural modulus and heat distortion temperature of the alloy are effectively maintained. This avoids the significant decrease in rigidity and heat resistance caused by traditional toughening methods, ensuring that the product does not deform and fail under high temperature load conditions. Detailed Implementation Preparation Example
[0030] Preparation Example 1 A silicon-containing PC is prepared by the following method: A1. Under vacuum of -0.1 MPa, 300 g of bisphenol A was placed in a reaction vessel, heated to 160°C, and then 300 g of dicarbonate (diphenyl carbonate) and 9 g of catalyst (dipotassium hydrogen phosphate) were slowly added. The reaction was kept at this temperature for 3 hours to obtain mixture 1. A2. Under vacuum conditions of -0.1 MPa, mixture 1, 45 g of polysiloxane diol and 6 g of zinc acetate were added to a reaction vessel. The temperature of the reaction vessel was raised to 220°C and the reaction was maintained for 6 hours. After post-processing, silicon-containing PC was obtained.
[0031] Polysiloxane diol has a molecular weight of 3000.
[0032] Preparation Example 2 A silicon-containing PC is prepared by the following method: A1. Under vacuum of -0.1 MPa, 300 g of bisphenol A was placed in a reaction vessel, heated to 170°C, and then 309 g of dicarbonate (xylene carbonate) and 12 g of catalyst (dipotassium hydrogen phosphate) were slowly added. The reaction was kept at this temperature for 3-5 hours to obtain mixture 1. A2. Under vacuum conditions of -0.1 MPa, mixture 1, 54 g of polysiloxane diol and 9 g of zinc acetate were added to a reaction vessel. The temperature of the reaction vessel was raised to 230°C and the reaction was maintained for 5 h. After post-processing, silicon-containing PC was obtained.
[0033] Polysiloxane diol has a molecular weight of 6000.
[0034] Preparation Example 3 A silicon-containing PC is prepared by the following method: A1. Under vacuum of -0.1 MPa, 300 g of bisphenol A was placed in a reaction vessel, heated to 180°C, and then 315 g of dicarbonate (dimethyl carbonate) and 15 g of catalyst (dipotassium hydrogen phosphate) were slowly added. The reaction was kept at this temperature for 5 h to obtain mixture 1. A2. Under vacuum conditions of -0.1 MPa, mixture 1, 60 g of polysiloxane diol and 12 g of zinc acetate were added to a reaction vessel. The temperature of the reaction vessel was raised to 240℃ and the reaction was maintained for 4 h. After post-processing, silicon-containing PC was obtained.
[0035] Polysiloxane diol has a molecular weight of 10,000.
[0036] Preparation Example 4 A silicon-containing PC, the difference between this preparation example and preparation example 1 is that the polysiloxane diol is composed of polysiloxane diol with a molecular weight of 3000 and polysiloxane diol with a molecular weight of 6000 in a weight ratio of 1:4.
[0037] Preparation Example 5 A silicon-containing PC, the difference between this preparation example and preparation example 1 is that the polysiloxane diol is composed of polysiloxane diol with a molecular weight of 6000 and polysiloxane diol with a molecular weight of 10000 in a weight ratio of 1:7.
[0038] Example The ABS selected is DG-417 from Tianjin Dagu Chemical Co., Ltd. PBT is selected from BASF's Ultradur® B 4300 G6.
[0039] The EMA-g-GMA is from Arkema, France, and its model number is AX8700.
[0040] The silane coupling agent modified mica powder is obtained by mixing nano-sized mica powder and γ-aminopropyltriethoxysilane at a weight ratio of 10:1.
[0041] Cellulose nanocrystals were selected from Shanghai Maclean Biochemical Technology Co., Ltd.
[0042] Example 1 A chemically resistant silicon-based PC-PBT-ABS ternary alloy material is prepared by the following method: The following ingredients from Preparation Example 1 were mixed: 475g of silicon-containing PC, 100g of ABS, 100g of PBT, 20g of modified toughening agent, 20g of high-rubber powder, 20g of silicone powder, 100g of flame retardant (potassium perfluorobutyl sulfonate), 150g of reinforcing agent (cellulose nanocrystals), 5g of antioxidant (Irganox 1010), and 10g of anti-dripping agent (polytetrafluoroethylene micro powder). The mixture was then added to a twin-screw extruder for extrusion granulation. The processing temperature of the twin-screw extruder was 220°C, and the screw speed was 250 rpm, resulting in a chemically resistant silicon-based PC-PBT-ABS ternary alloy material.
[0043] The modified toughening agent is composed of EMA-g-GMA and silane coupling agent modified mica powder in a weight ratio of 5:1.
[0044] Example 2 A chemically resistant silicon-based PC-PBT-ABS ternary alloy material is prepared by the following method: The following ingredients from Preparation Example 2 were mixed: 547g of silicon-containing PC, 90g of ABS, 90g of PBT, 15g of modified toughening agent, 15g of high-rubber powder, 15g of silicone powder, 85g of flame retardant (zinc diethylphosphinate), 120g of reinforcing agent (cellulose nanocrystals), 8g of antioxidant (Irganox 1010), and 15g of anti-dripping agent (polytetrafluoroethylene micro powder). The mixture was then added to a twin-screw extruder for extrusion granulation. The processing temperature of the twin-screw extruder was 250°C, and the screw speed was 280 rpm, resulting in a chemically resistant silicon-based PC-PBT-ABS ternary alloy material.
[0045] The modified toughening agent is composed of EMA-g-GMA and silane coupling agent modified mica powder in a weight ratio of 5:1.5.
[0046] Example 3 A chemically resistant silicon-based PC-PBT-ABS ternary alloy material is prepared by the following method: The following ingredients from Preparation Example 3 were mixed: 10g of silicon-containing PC, 80g of ABS, 80g of PBT, 10g of modified toughening agent, 10g of high-rubber powder, 10g of silicone powder, 70g of flame retardant (aluminum diethylphosphinate), 100g of reinforcing agent (cellulose nanocrystals), 10g of antioxidant (Irganox 1010), and 20g of anti-dripping agent (polytetrafluoroethylene micro powder). The mixture was then added to a twin-screw extruder for extrusion granulation. The processing temperature of the twin-screw extruder was 280°C, and the screw speed was 300 rpm, resulting in a chemically resistant silicon-based PC-PBT-ABS ternary alloy material.
[0047] The modified toughening agent is composed of EMA-g-GMA and silane coupling agent modified mica powder in a weight ratio of 5:2.
[0048] Example 4 A chemically resistant silicon-based PC-PBT-ABS ternary alloy material. The difference between this embodiment and Embodiment 1 is that the reinforcing agent is composed of cellulose nanocrystals, nano-clay and nano-rare earth oxides (cerium oxide) in a weight ratio of 10:4:1.
[0049] The average particle size of cellulose nanocrystals is 150 nm, the average particle size of nanoclay is 200 nm, and the average particle size of nanorare earth oxides (cerium oxide) is 50 nm.
[0050] Example 5 A chemically resistant silicon-based PC-PBT-ABS ternary alloy material. The difference between this embodiment and Embodiment 1 is that the reinforcing agent is composed of cellulose nanocrystals, nano-clay and nano-rare earth oxides (cerium oxide) in a weight ratio of 10:7:1.
[0051] The average particle size of cellulose nanocrystals is 150 nm, the average particle size of nanoclay is 200 nm, and the average particle size of nanorare earth oxides (cerium oxide) is 50 nm.
[0052] Example 6 A chemically resistant silicon-based PC-PBT-ABS ternary alloy material. The difference between this embodiment and Embodiment 4 is that the average particle size of the cellulose nanocrystals is 150 nm, the average particle size of the nano-clay is 150 nm, and the average particle size of the nano-rare earth oxides (cerium oxide) is 150 nm.
[0053] Example 7 A chemically resistant silicon-based PC-PBT-ABS ternary alloy material, the difference between this embodiment and Example 1 is that the reinforcing agent is composed of cellulose nanocrystals and nano-clay in a weight ratio of 10:4.
[0054] The average particle size of cellulose nanocrystals is 150 nm, and the average particle size of nanoclay is 200 nm.
[0055] Example 8 A chemically resistant silicon-based PC-PBT-ABS ternary alloy material, the difference between this embodiment and Example 1 is that cellulose nanocrystals are replaced with silicon dioxide of equal particle size.
[0056] Example 9 A chemically resistant silicon-based PC-PBT-ABS ternary alloy material. The difference between this embodiment and Example 1 is that the silicon-containing PC is from Preparation Example 4.
[0057] Example 10 A chemically resistant silicon-based PC-PBT-ABS ternary alloy material. The difference between this embodiment and Example 1 is that the silicon-containing PC is from Preparation Example 5.
[0058] Example 11 A chemically resistant silicon-based PC-PBT-ABS ternary alloy material. The difference between this embodiment and Example 1 is that the silicon-containing PC is DHMY460 from Daehan High Performance Materials (Guangdong) Co., Ltd.
[0059] Example 12 A chemically resistant silicon-based PC-PBT-ABS ternary alloy material. The difference between this embodiment and Embodiment 1 is that the silicon-containing PC content is 495g, the ABS content is 80g, and the PBT content is 100g.
[0060] Comparative Example Comparative Example 1 A chemically resistant silicon-based PC-PBT-ABS ternary alloy material. The difference between this comparative example and Example 1 is that the silane coupling agent modified mica powder is replaced with an equal weight of methyl methacrylate-butadiene-styrene ternary copolymer.
[0061] The methyl methacrylate-butadiene-styrene terpolymer is M-724, from the Kane Ace® series of Kanebuchi, Japan.
[0062] Comparative Example 2 A chemically resistant silicon-based PC-PBT-ABS ternary alloy material, the difference between this comparative example and Example 1 is that the toughening agent is a methyl methacrylate-butadiene-styrene ternary copolymer.
[0063] Comparative Example 3 A chemically resistant silicon-based PC-PBT-ABS ternary alloy material. The difference between this comparative example and Example 1 is that no high-polymer powder is added.
[0064] Comparative Example 4 A chemically resistant silicon-based PC-PBT-ABS ternary alloy material. The difference between this comparative example and Example 1 is that no reinforcing agent is added.
[0065] Detection methods / test methods The chemically resistant silicon-based PC-PBT-ABS ternary alloy materials obtained in Examples 1-12 and Comparative Examples 1-4 were made into sheets, and the following experiments were conducted: Impact strength: Tested in accordance with ISO 180-2023.
[0066] Tensile strength and elongation at break: tested in accordance with ISO 527-1-2019.
[0067] Chemical resistance test: The sheet was immersed in a mixed solution of ethyl acetate and ethanol (volume ratio = 1:1), and the time before cracking began to appear was calculated. A longer time indicates better chemical resistance. Experimental data are shown in Table 1. Table 1. Experimental data of Examples 1-12 and Comparative Examples 1-4
[0068] As can be seen from the above data, the chemically resistant silicon-based PC-PBT-ABS ternary alloy material prepared by the formula and process in this application has good notched impact strength, tensile strength and chemical resistance, and achieves a synergistic improvement in toughness, rigidity and chemical resistance.
[0069] As can be seen from the comparison between Example 1 and Comparative Examples 1-4, after MBS was completely replaced by the modified toughening agent in Comparative Examples 1-2, the impact strength and chemical resistance both decreased, the toughness of Comparative Example 3 decreased, and the tensile strength and chemical resistance of Comparative Example 4 decreased significantly. It can be seen that this application effectively solves the problems of poor compatibility, imbalance of toughness and rigidity and insufficient chemical resistance caused by traditional physical blending of silicon-based modification through the synergistic effect of specific modified toughening agents, high-resin powder and reinforcing agents.
[0070] Compared with Examples 1 and Examples 4-8, the tensile strength and chemical resistance of Examples 4-5 are significantly improved, while the properties of Examples 6 are significantly reduced. In Example 8, the toughness and chemical resistance decrease after replacing cellulose nanocrystals with silica. It can be seen that the gradient-graded ternary nano-reinforcement network composed of cellulose nanocrystals, nano-clay and nano-rare earth oxides of different particle sizes can achieve a balance between the rigidity, toughness and chemical resistance of the material.
[0071] Compared with Examples 1 and 9-11, by combining high and low molecular weight polysiloxane diols, the low-temperature toughness and elongation at break of the alloy can be maximized while maintaining high chemical resistance.
[0072] Comparing Examples 1 and 12, it is evident that the ratio of PC, PBT, and ABS needs to be synergistically optimized among mechanical properties, chemical resistance, and processing fluidity. Simply increasing the content of silicon-containing PC can enhance rigidity and chemical resistance, but it will reduce toughness.
[0073] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A chemically resistant silicon-based PC-PBT-ABS ternary alloy material, characterized in that, It is prepared from the following raw materials in parts by weight: Silicon-containing PC 47.5-61% ABS 8-10% PBT8-10% Modified toughening agent 1-2% 1-2% high-gluten powder Silicone powder 1-2% Flame retardant 7-10% 10-15% enhancer Antioxidant 0.5-1% Anti-dripping agent 1-2% The modified toughening agent is composed of EMA-g-GMA and silane coupling agent modified mica powder.
2. The chemically resistant silicon-based PC-PBT-ABS ternary alloy material according to claim 1, characterized in that: The reinforcing agent is composed of cellulose nanocrystals, nanoclay, and nanorare earth oxides in a weight ratio of 10:4-7:
1.
3. The chemically resistant silicon-based PC-PBT-ABS ternary alloy material according to claim 2, characterized in that: The cellulose nanocrystals, the nanoclay, and the nanorare earth oxides have different particle sizes.
4. The chemically resistant silicon-based PC-PBT-ABS ternary alloy material according to claim 1, characterized in that, The silicon-containing PC is prepared by the following method: A1. Under vacuum conditions, bisphenol A is placed in a reaction vessel, heated to 160-180℃, and then slowly added with diester and catalyst. The reaction is maintained at this temperature for 3-5 hours to obtain mixture 1. A2. Under vacuum conditions, mixture 1, polysiloxane diol and zinc acetate are added to a reaction vessel. The temperature of the reaction vessel is raised to 220-240℃ and kept at this temperature for 4-6 hours. The resulting product is silicon-containing PC after post-processing.
5. The chemically resistant silicon-based PC-PBT-ABS ternary alloy material according to claim 4, characterized in that, The raw materials used to prepare the silicon-containing PC are as follows (parts by weight): 100 parts of Bisphenol A 100-105 parts of dicarbonate Catalyst 0.3-0.5 parts 15-20 parts of polysiloxane diol Zinc acetate 0.2-0.4 parts.
6. The chemically resistant silicon-based PC-PBT-ABS ternary alloy material according to claim 4, characterized in that: The polysiloxane diol is composed of polysiloxane diol with a molecular weight of 3000-6000 and polysiloxane diol with a molecular weight of 6000-10000 in a weight ratio of 1:4-7.
7. The chemically resistant silicon-based PC-PBT-ABS ternary alloy material according to claim 1, characterized in that: The silicon-containing PC content is 49.5%, the ABS content is 8%, and the PBT content is 10%.
8. The chemically resistant silicon-based PC-PBT-ABS ternary alloy material according to claim 1, characterized in that: The flame retardant includes at least one of sulfonates, phosphates, and phosphonates.
9. The chemically resistant silicon-based PC-PBT-ABS ternary alloy material according to claim 1, characterized in that: The anti-dripping agent includes at least one of polytetrafluoroethylene micropowder, PTFE-coated silicone rubber core-shell particles, siloxane-acrylate core-shell particles, and polyimide micropowder.
10. A method for preparing a chemically resistant silicon-based PC-PBT-ABS ternary alloy material as described in any one of claims 1-9, characterized in that, The preparation steps include the following: Silicon-containing PC, ABS, PBT, modified toughening agent, high-rubber powder, silicone powder, flame retardant, reinforcing agent, antioxidant and anti-dripping agent are mixed and added to a twin-screw extruder for extrusion granulation to obtain a chemically resistant silicon-based PC-PBT-ABS ternary alloy material.